Prophetic identities : indigenous missionaries on British colonial frontiers, 1850-75 - Bradford, Justin Tolly, 1976- (UBC Press, 2012)
"The spread of Christianity is often presented as a story of conquest, of powerful European missionaries waging a cultural assault on hapless indigenous victims. Yet the presence of indigenous men among missionary ranks in the nineteenth century complicates these narratives. What compelled these individuals to embrace Christianity? How did they reconcile being both Christian and indigenous in an age of empire?